PENGARUH CAPITAL STRUKTUR, CASH FLOW AND LIQUIDITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN SUB SEKTOR TEKSTILYANG TERDAFTAR DI BURSA EFEKINDONESIA PERIODE 2013-2017 - Tampubolon, Lasma Ria; Simamora, Osnidar; Sidabutar, Isa Handayani; Sibagariang, Kristina (Yayasan Akrab Pekanbaru, 2019)
The objective is to test and analyze the influence of Capital struktur, Cash Flow and Liquidity on firm value of Sub Sektor Otomotif and Sub Sektor Tekstil companies found in Indonesia Stock Exchange in period 2013-2017. The approach used in this study is a quantitative approach, the type of research used is descriptive quantitative and the nature of this research is the causal reletionship. The method of selecting this research sample using a purposive sampling method. The results of this test indicate that capital struktur has a negative and significant effect on firm value and liquidity does not have a significant effect firm value.